PERBEDAAN KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN MENGGUNAKAN PERMAINAN TEBAK GAMBAR BERBASIS APLIKASI SCRATCH JR DI TK KASIH BAPA PERCUT - Marcelita Nainggolan; Isa Hidayati (STKIP Subang, 2026)
Speaking ability is one aspect of language development that needs to be developed from an early age because it plays an important role in children's ability to communicate, convey ideas, and interact with the environment. Based on the results of observations at Kasih Bapa Percut Kindergarten, the speaking ability of children aged 5–6 years is still not optimally developed so that more innovative learning media is needed. This study aims to determine the effect of using a guessing game based on the Scratch Jr application on the speaking ability of children aged 5–6 years at Kasih Bapa Percut Kindergarten. The study used a quantitative approach with the Pre-Experimental Design method using the One Group Pretest–Posttest Design. The research sample consisted of 15 children selected using the total sampling technique. Data collection was carried out through observation sheets, then analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The results showed that the average speaking ability of children increased from 22.2 at the pretest to 32.8 at the posttest. The results of the hypothesis test showed an Asymp. Sig. value. (2-tailed) = 0.000 (<0.05), indicating a significant effect of the use of the Scratch Jr. application-based picture guessing game on the speaking skills of children aged 5–6 years. Improved speaking skills were seen in children's ability to name pictures, describe object characteristics, answer questions, construct simple sentences, and retell information coherently. Therefore, the Scratch Jr. application-based picture guessing game can be used as an effective alternative learning medium to improve the speaking skills of early childhood.